Vibrational Characterization and Antioxidant Activity of Newly Synthesized Gallium(III) Complex - Irena Kostova; Venceslava Atanasova; Magdalena Spasova Kondeva-Burdina; Virginia Iordanova Tzankova (Open Journal of Chemistry - Peertechz Publications, 2016)
The gallium(III) complex of orotic acid (HOA) was synthesized and its structure was determined by means of analytical and spectral analyses. Detailed vibrational analysis of HOA, sodium salt of HOA (NaOA) and Ga(III)-OA systems based on both the calculated and experimental spectra confi rmed the suggested metal-ligand binding mode. Signifi cant differences in the IR and Raman spectra of the complex were observed as compared to the spectra of the ligand and confi rmed the suggested metal-ligand binding mode. The calculated vibrational wavenumbers including IR and Raman scattering activities for the ligand and its Ga(III) complex were in good agreement with the experimental data. The vibrational analysis performed for the studied species, orotic acid, sodium salt of orotic acid and its Ga(III) complex, helped to explain the vibrational behaviour of the ligand vibrational modes, sensitive to interaction with Ga(III). The compounds HOA, NaOA and GaOA were investigated for possible antioxidant activity in a model of non-enzyme-induced lipid peroxidation on isolated rat microsomes. On isolated rat microsomes, administered alone, the compounds didn't revealed pro-oxidant effects. In conditions of non-enzymeinduced lipid peroxidation, only the complex GaOA showed antioxidant activity. HOA and NaOA didn't reveal antioxidant activity. We suggest that the antioxidant activity of the complex GaOA, might be due to the presence of gallium in the structure of GaOA.